Entrepreneurship and small business development in China. - Li, Dr Jun (Volume 13, Issue 2., 2006)
This ebook focuses upon advances in entrepreneurship and small business development taking place within specific geographic areas. By most accounts, China's economic growth over the past two decades has been impressive, and Small and Medium-Sized Enterprises (SMEs) played a vital role in the well known success story of the contemporary Chinese economy. It appears, however, that many myths still circulate in relation to the scope, extent and impact of entrepreneurship in China. Despite increasing interest in Chinese entrepreneurial practices, research in this important topic of study remains re.